Comparison of efficacy and safety between benidipine and hydrochlorothiazide in fosinopril-treated hypertensive patients with chronic kidney disease: protocol for a randomised controlled trial. Issue 2 (24th February 2017) - Xue, Cheng; Zhou, Chenchen; Yang, Bo; Lv, Jiayi; Dai, Bing; Yu, Shengqiang; Wang, Yi; Zhao, Guanren; Mei, Changlin
Abstract : Introduction: Co-administration of a diuretic or calcium channel blocker with an ACE inhibitor are both preferred combinations in patients with hypertensive chronic kidney disease (CKD). According to the available evidence, it is still unknown which combination plays a more active role in renal protection. We hypothesised that a combination of fosinopril and benidipine may delay the progression of CKD more effectively than a combination of fosinopril and hydrochlorothiazide (HCTZ). Methods and analysis: This study will be a multicentred, prospective, double-blind, randomised parallel controlled trial for hypertensive CKD patients in China. Patients will be randomised to one of two treatment groups: a combination of benidipine 4–8 mg/day and fosinopril 20 mg/day; or a combination of HCTZ 12.5–25 mg/day and fosinopril 20 mg/day. Patients will be followed up for 24 months after a month's fosinopril run-in. There will be dose-titration after 1 and 2 months. The primary endpoint is changes in estimated glomerular filtration rate (eGFR) from baseline to month 24. Secondary endpoints include changes in home blood pressure (BP), ambulatory BP, proteinuria, urinary albumin/creatinine ratio, and composite renal events in 24 months. Inclusion criteria are: age 18–80 years, non-dialysis CKD patients with eGFR >30 mL/min/1.73 m 2, home BP >130 mm Hg systolic or BP >80 mm Hg diastolic at the screening and randomisation, and 24 hour proteinuria <3.5 g. Principal exclusions are hypertensive crisis, transplantation, cancer, severe diabetes complications, hyperkalaemia and severe allergy. The required sample size was 511 patients for detecting a difference in the change of eGFR (one sided α=0.025, power 1-β=0.90). Ethics and dissemination: BEAHIT (Benidipine and Hydrochlorothiazide in Fosinopril Treated Chronic Kidney Disease Patients with Hypertension) was approved by Changzheng Hospital Ethics Committee (CZ-20160504-16). The outcomes will be published in a peer-reviewed journal. Trial registration number: NCT02646397.